2009
DOI: 10.1364/ao.48.000h77
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in three-dimensional information processing based on integral imaging

Abstract: Recently developed integral imaging techniques are reviewed. Integral imaging captures and reproduces the light rays from the object space, enabling the acquisition and the display of the three-dimensional information of the object in an efficient way. Continuous effort on integral imaging has been improving the performance of the capture and display process in various aspects, including distortion, resolution, viewing angle, and depth range. Digital data processing of the captured light rays can now visualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
192
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 370 publications
(193 citation statements)
references
References 87 publications
0
192
0
1
Order By: Relevance
“…In these devices, the content of the image plane can be treated as a two-dimensional (2D) representation of a photographed/ computer-generated 3D scene. Depending on the device type, this image is called differently: a multiview image [6], an integral image [7,8], a light-field image [9], or a plenoptic image [10]. Some plenoptic cameras are already available in the market [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In these devices, the content of the image plane can be treated as a two-dimensional (2D) representation of a photographed/ computer-generated 3D scene. Depending on the device type, this image is called differently: a multiview image [6], an integral image [7,8], a light-field image [9], or a plenoptic image [10]. Some plenoptic cameras are already available in the market [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It thus provides both horizontal and vertical parallax with quasi-continuous viewpoints within the viewing angle. 6 That convenience makes it a candidate for next-generation 3D TVs that viewers can enjoy watching from any position they like. To image them, near or far, in focus with that convergence reflex, the thickness and curvature of the eyes' lenses (gray) must also change.…”
Section: Autostereoscopymentioning
confidence: 99%
“…It has been reported that these parameters exhibit a trade-off relationship [2]. Since the first proposal by Lippmann, integral imaging systems have been further developed and improved by many research groups [3][4][5].…”
Section: Introductionmentioning
confidence: 99%